2020
DOI: 10.1111/1750-3841.15382
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the NaCl diffusion in beef during brining process

Abstract: An in‐depth understanding of mass transfer during brining process is important for improving the quality and characteristics of meat products. In this study, a fitted equation of time and NaCl concentrations in the aqueous phase of beef was established to calculate the NaCl diffusion coefficient for simulation. A three‐dimensional simulating model of mass transfer was developed to evaluate the NaCl diffusion in beef during brining process. And the validity of this simulating model was verified by comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…The power and exponential functions (R 2 > 0.9500) are good for correlations when the linear function is poor (R 2 < 0.7). The results obtained in this study agree with previous studies [ 39 ], which proves that the data predicted by the power function time-varying model are closer to the De value calculated using the experimental method, and the experimental data were a good fit with predicted values. Additionally, when xylitol was added (0–12%), the experimentally calculated De values were 1.29 × 10 −9 m 2 ·s −1 , 1.22 × 10 −9 m 2 ·s −1 , 1.2 × 10 −9 m 2 ·s −1 , and 1.15 × 10 −9 m 2 ·s −1 ( Figure 2 d).…”
Section: Resultssupporting
confidence: 91%
“…The power and exponential functions (R 2 > 0.9500) are good for correlations when the linear function is poor (R 2 < 0.7). The results obtained in this study agree with previous studies [ 39 ], which proves that the data predicted by the power function time-varying model are closer to the De value calculated using the experimental method, and the experimental data were a good fit with predicted values. Additionally, when xylitol was added (0–12%), the experimentally calculated De values were 1.29 × 10 −9 m 2 ·s −1 , 1.22 × 10 −9 m 2 ·s −1 , 1.2 × 10 −9 m 2 ·s −1 , and 1.15 × 10 −9 m 2 ·s −1 ( Figure 2 d).…”
Section: Resultssupporting
confidence: 91%
“…Zhao et al (2020) reported a very similar salt Deff (8.51 × 10 -10 m 2 /s) during the wet salting (6 % NaCl, 20ºC) of beef samples.Similarly, Aykın-Dinçer & Erbaş (2018) reported a water Deff value of 2.40 × 10 -10 m 2 /s in the dry-salting (20 g NaCl/100 g d.b.) of beef slices (3.5 mm).…”
mentioning
confidence: 72%
“…The NaCl effective diffusion coefficient (De) was calculated by Equation (5) (Zhao et al., 2020), which was the integrated solution of Fick's second law (Crank, 1975). The samples were considered as an isothermal semi‐infinite geometry slab with unidirectional mass transfer.…”
Section: Methodsmentioning
confidence: 99%